2022
DOI: 10.1149/1945-7111/ac5ff2
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic Coupling of Copper and Carbon Steel in the Presence of Bentonite Clay and Chloride

Abstract: The long-term containment plan for Canada’s used nuclear fuel employs copper-coated carbon steel (CS) containers encased in compacted bentonite clay buffer boxes. In the hypothetical case of a through-coating defect, galvanic interactions between the Cu coating and the CS vessel are dependent on the conditions at the container surface. A zero-resistance ammeter was used to measure the galvanic current between Cu and CS electrodes at various area ratios in the presence of aerated 1 M NaCl and obstructive layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, a larger current is generated when the Cu:CS area ratio is as large as 1000. [12,13] Our study using Cu electrical resistance sensors corrosion under oxic conditions in bentonite with Aspö groundwater resulted in a corrosion rate of around 1 μm year -1 monitored through 3.5 years of exposure. [14,15] There, the reduction of thickness and impedance measurements were used to evaluate the corrosion rate on copper electrical resistance sensors.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, a larger current is generated when the Cu:CS area ratio is as large as 1000. [12,13] Our study using Cu electrical resistance sensors corrosion under oxic conditions in bentonite with Aspö groundwater resulted in a corrosion rate of around 1 μm year -1 monitored through 3.5 years of exposure. [14,15] There, the reduction of thickness and impedance measurements were used to evaluate the corrosion rate on copper electrical resistance sensors.…”
Section: Introductionmentioning
confidence: 95%
“…In the event of an undetected defect in the Cu coating, the underlying CS could be exposed to the groundwater, potentially accelerating the galvanical corrosion of CS. [10][11][12][13] Recent studies have simulated a defect in a coldsprayed coating and reported that corrosion proceeds via the galvanic coupling and oxygen reduction at the surface. [10,11] Besides the accumulation of damage at the base of the defect, corrosion propagated along the copper/steel interface, most likely resulting from damage inflicted during the deposition process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a common place for this element in equivalent circuits is a series connection with R ct although the cases of its placement in other positions are not rare. Positioning the Warburg impedance away from the R ct has been proposed by other authors in various equivalent circuits describing some specific processes at Li-ion batteries [44,45] and electroactive species diffusion through modified with polymers electrode surfaces for biosensing [46] or diffusion of O 2 through above 2 mm bentonite clay layer on carbon steel [47]. To achieve better fits to our experimental results, the Warburg impedance is added in series of R Ox , which indicates that diffusion limitations are localised at the electrolyte-oxide film interface.…”
Section: Corrosion Behaviour Of Sb-cu Layers At Open Circuit Potentialmentioning
confidence: 99%